# math

How do I find the quotient of x/2y and (2xy)^2/9xy^3

1. 👍 0
2. 👎 0
3. 👁 56
asked by Ellie
1. if top = (x/2y)
and
bottom = [ (2xy)^2/9xy^3 ]
multiply top and bottom by 18 x y^3

1. 👍 0
2. 👎 0
posted by Damon

## Similar Questions

1. ### Math-divide Polynomial

need to find the quotient and remainder. x^3+x^2y-9xy^2-9y^3 / x+y

asked by vicky on May 7, 2012
2. ### JAD

(4x² - 2xy + y²) + (- 8x² -9xy – y²) + (x² + xy -8y²)

asked by Anonymous on April 23, 2011
3. ### Math-helpppppp

1)when a certain polynomial is divided by x - 3, the quotient is x^2+2x-5 and the remainder is -3. what is the polynomial 2) Find each quotient and remainder. Assume the divisor is not equal to zero. a)(2x^2+29x-x^3-40)/(-3+x)

asked by sarah on April 28, 2012
4. ### Math--help help help

1)when a certain polynomial is divided by x - 3, the quotient is x^2+2x-5 and the remainder is -3. what is the polynomial 2) Find each quotient and remainder. Assume the divisor is not equal to zero. a)(2x^2+29x-x^3-40)/(-3+x)

asked by sarah on April 28, 2012
5. ### Algebra

Could someone help me with this question Simplify the rational expression. (3x^2y+9xy^2-12y^3)/(36x^3y-27x^2y^2-9xy^3)

asked by Alex on September 26, 2010
6. ### Algebra

Could someone help me with this question Simplify the rational expression. (3x^2y+9xy^2-12y^3)/(36x^3y-27x^2y^2-9xy^3)

asked by Alex on September 26, 2010
7. ### pre-cal

Use Pascal's triangle to expand the expression. (x − y)5 so I tried to work this out: (x-y)^5 = [(x-y)(x-y)][(x-y)(x-y)](x-y) (x-y)^2 = (x-y)(x-y) = x^2 - 2xy + y^2 x^2 - 2xy + y^2)(x^2 - 2xy + y^2) = x^4 -4x^3y + 6x^2y^2 -

asked by James on August 12, 2015
8. ### Algebra

Simplify (2xy^2+3)((2xy^2)^2-(2xy^2)(3)+(3)^2) This reminds me of (U+a)(U^2- aU + a^2). When mulipltiplied out, one gets a cubic equation. Do you remember the formula for factoring the sum of two cubes? a^3+b^3= ????

asked by Juri on August 9, 2007
9. ### mathematics

If 3xy^3 - 4x = 10y^2, find y ' (x) a) (4 + 3y^2)/(9xy^2 + 20y) b) (4 - 3y^2)/(9xy^2 - 20y) c) (3 + 4y^2)/(20xy^2 + 9y) d) (3 - 4y^2)/(20xy^2 - 9y)

asked by Donna on May 11, 2008
10. ### Calculus

Find y" by implicit differentiation. x^3+y^3 = 1 (x^3)'+(y^3)' = (1)' 3x^2+3y^2(y') = 0 3y^2(y') = -3x^2 y' = -3x^2/3y^2 y' = -x^2/y^2 y" = [(y^2)(-x^2)'-(-x^2)(y^2)']/y^4 y" = [(y^2)(-2x)-(-x^2)(2y)]/y^4 y" =

asked by Justin on September 27, 2015

More Similar Questions